2022
DOI: 10.3390/rs14041032
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Lake Volume Changes (2003–2020) and Driving Forces at a Global Scale

Abstract: Lakes play a key role in the global water cycle, providing essential water resources and ecosystem services for humans and wildlife. Quantifying long-term changes in lake volume at a global scale is therefore important to the sustainability of humanity and natural ecosystems. Yet, such an estimate is still unavailable because, unlike lake area, lake volume is three-dimensional, challenging to be estimated consistently across space and time. Here, taking advantage of recent advances in remote sensing technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…This improvement could be explained by the fact that the hypsometry of this study exhibits much stronger area-level correlations than that of Y. Feng et al (2022). For example, the median R 2 increased from 0.43 to 0.93 (Figure 9b).…”
Section: Impact Of Hypsometry On Water Level Reconstructionmentioning
confidence: 75%
See 3 more Smart Citations
“…This improvement could be explained by the fact that the hypsometry of this study exhibits much stronger area-level correlations than that of Y. Feng et al (2022). For example, the median R 2 increased from 0.43 to 0.93 (Figure 9b).…”
Section: Impact Of Hypsometry On Water Level Reconstructionmentioning
confidence: 75%
“…Despite recent advances on documenting long-term changes in lake water storage (Y. Feng et al, 2022;Luo et al, 2022;Yao et al, 2023), water storage data are unavailable for most small water bodies and poorly constrained for some large lakes due to simplified hypsometries or empirical models (Table 1). The level reconstruction method here can be combined with lake area data sets (Pi et al, 2022;Yao et al, 2019;Zhao & Gao, 2018) to fill this data gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICESat/GLAS data validation on Dongting Lake shows that the ICESat/GLAS data processing method is suitable for obtaining water level control points in large lakes [14]. A study of global lakes larger than 10 km2 has shown that ICESat and ICESat-2 measurement errors are lower than radar measurements such as Topex/Poseidon, ENVISAT, CryoSat-2, etc [15]. Although ICESat and ICESat-2 have been used to study lake levels, they have yet to be applied to studying the effects of water diversion on lakes, especially those in densely populated lake areas.…”
Section: Introductionmentioning
confidence: 99%